Inclusive Learning 365 : Edtech Strategies for Every Day of the Year - Bugaj, Christopher R.; Poss, Beth; Marotta, Mike; Janowski, Karen (Book collections on Project MUSE., 2021)
"Educators across the world are working to design individualized instruction that empowers every student to become experts at learning. Technology and instructional interventions designed to support students with disabilities often eventually become mainstream and used by the masses. These practices provide a pathway for designing inclusive, equitable and accessible educational experiences that meet the needs of every individual learner. This engaging book includes daily strategies accompanied by examples of tools that can be implemented immediately to design meaningful instruction. Topics covered include role-playing games for social-emotional learning, building literacy through captioned video, coding to teach early literacy, text-to-speech for math and reading, and much more! The heart of the book is the shift in mindset that occurs by exploring a different practical, inclusive strategy each day and infusing these strategies into everyday practice.""--